Cancers in people with HIV and AIDS : progress and challenges - Yarchoan, Robert (Springer New York, 2014)
The association between AIDS and cancer was recognized from the beginning ofthe AIDS epidemic, when the appearance of Kaposi sarcoma in a cluster of youngmen was one of the first signs of this new disease. It was soon recognized that AIDSpatients are prone to develop a number of "AIDS-defining" cancers: Kaposi sarcoma,lymphoma, and cervical cancer. The development of effective combination anti-HIVtherapy starting around 1996 converted AIDS from a death sentence to a manageabledisease and led to dramatic shifts in the epidemic. As this therapy was able to improveimmune function in patients, the incidence of most "AIDS-defining" cancers decreased.There is a misconception, however, that AIDS has gone away. In fact, as AIDS patientsare living longer, the number of AIDS patients has more than doubled in the UnitedStates since 1996, and the AIDS population overall has increased in age. Also, as AIDSpatients are less likely to die of other complications, cancer is coming to the forefront as one of the most common causes of death in regions where AIDS drugs are widelyavailable.Moreover, the three "AIDS-defining" cancers are now taking a back seat toa number of other HIV-associated cancers, such as Hodgkin lymphoma, lung cancer,and anal cancer. In the developing world, AIDS-associated cancers are a major publichealth problem, and in some regions of sub-Saharan Africa, Kaposi sarcoma is themost common tumor in men. In recent years, there has been a vast increase in our understanding of HIV-associatedcancers. We now know, for example, that most are caused by other viruses and thatthe main role of HIV and immunodeficiency is to provide a supportive environmentfor the viruses to multiply and for the cancers to develop. But there remain a numberof unanswered questions and a need for improved prevention and therapy. In the 28chapters of this book, written by some of the most renowned experts in this field, wepresent up-to-date information on the cancers associated with HIV infection. Thechapters cover the epidemiology of these cancers, as well as their pathogenesis, clinicalpresentation, and treatment. Dr. Robert Yarchoanis the Director of the Office of HIV and AIDS Malignancy andChief of the HIV and AIDS Malignancy Branch in the National Cancer Institute. Heplayed a major role in developing the first AIDS drugs. His research is now focused onAIDS-related cancers, especially Kaposi sarcoma and other cancers caused by Kaposisarcoma-associated herpesvirus.